Carbon sequestration rate modelling system for hotel and resort green spaces - Othman, Rashidi; Hashim, Khairusy Syakirin Has-Yun; Hj. Baharuddin, Zainul Mukrim; Mahamod, Lukman Hakim (2015)
Carbon dioxide (CO2) emission in urban area is high due to the presence of numerous emission sources in a confined space. Urban building management team such as urban hotel have to tackle this critical issue in order to maintain their hotel environmental quality. Increasing carbon rate in hotel atmosphere will distress the environment quality and will lead to serious global warming and other associated terrifying consequences. Landscape plant materials perhaps can provide a green solution to urban hotel carbon emission issue. Plant materials are natural agents for carbon dioxide sequestration, as well as other greenhouse gases. By proposing precise numbers of green area in a building, sufficient amount of carbon can be sequestered from the air. Corresponding to this phenomenon, various methodologies for trees as carbon sequestration calculations evolving and emerging as an important tool for greenhouse gas management. Conversely, study which concentrate on carbon sequestration calculation rate based on a single hotel building is still ambiguous. Therefore, this research will take a step forward by exploring the potential of carbon sequestration rate modelling and calculator for landscape plant materials at hotel buildings.